Coretta Scott - Shange, Ntozake; Nelson, Kadir (New York : Amistad/Katherine Tegen Books, 2009)
An illustrated biography of Coretta Scott King, describing her childhood in the segregated South, her marriage to Martin Luther King, Jr., and her civil rights work.
Wilson's Children, October 2010.
School Library Journal starred, January 2009.
Book Links (A.L.A.), October 2009.
Booklist starred, January 2009.
Book Links-starred, March 2009.
Pub Weekly, December 2008.
Keywords: King, Coretta Scott, -- 1927-2006 -- Juvenile literature; King, Martin Luther, -- Jr., -- 1929-1968 -- Juvenile literature; King, Coretta Scott, -- 1927-2006.; King, Martin Luther, -- Jr., -- 1929-1968.; Civil rights workers -- United States -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; African American women civil rights workers -- Biography -- Juvenile literature; African Americans -- Civil rights -- History -- 20th century -- Juvenile literature; Civil rights movements -- United States -- History -- 20th century -- Juvenile literature; Civil rights workers; African Americans -- Biography; African Americans -- Civil rights -- History; Civil rights movements -- History; Civil rights workers -- Biography; Women -- Biography; African Americans -- Women -- Biography; Nonfiction picture books